Correlations of WO3 species and structure with the catalytic performance of the selective oxidation of cyclopentene to glutaraldehyde on WO3/TiO2 catalysts - Lu, G.; Li, Xin Yong; Qu, Z.; Zhao, Q.; Li, H.; Shen, Y.; Chen, G. (Elsevier BV, 2010)
A series of WO3/TiO2 catalysts were synthesized by ultrasonic impregnation method using as-prepared TiO2 microspheres as support as a function of tungsten oxide species loading. The crystalline structure, molecular structure and the interaction with the support of the supported tungsten oxide phase were characterized by various techniques (scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), Raman, X-ray photoelectron spectroscopy (XPS) and specific surface areas (BET)), and their effects on the catalytic performance in selective oxidation of cyclopentene to glutaraldehyde were investigated. It was found that highly dispersed WO3 species were obtained on the surface of TiO2, and only W(VI) oxidation state was present on the support. The WO3/TiO2 catalysts showed high catalytic activity for selective oxidation of cyclopentene to glutaraldehyde. The catalytic activity increased with the WO3 loading, and reached maximum on the catalysts with the WO3 loading of 15-20 wt%. The molecular structures of calcinated tungsten oxide phase were determined to be tetrahedral surface tungsten oxide species with the WO3 loading below 20 wt%, and both Brönsted acid sites and Lewis acid sites were present on the surface of the catalysts. The strong support effect on the dispersion and molecular structure of WO3 as well as the Brönsted acid observed in the present work may have important catalytic implication. Further increasing the WO3 loading resulted in the decrease of catalytic performance of the catalyst, meanwhile the crystalline WO3 nanoparticles were present on the surface of the support. These reactivity trends showed the influence of molecular structure of WO3 on the surface of TiO2 support on the selective oxidation activity of cyclopentene to glutaraldehyde. © 2010 Elsevier B.V. All rights reserved.